Composição florística, estrutura horizontal e ecologia funcional de espécies arbóreas da floresta de igapó no Parque Nacional de Anavilhanas – AM - (:unkn) unknown (Universidade Federal do Amazonas, 2021)
Igapó forests are considered to be one of the highest priority environments for conservation actions. The present study aimed to increase the information on the diversity and distribution of tree plant species that occur on the islands that are periodically flooded by the waters of the Rio Negro of the Anavilhanas National Park, through the record of the forest composition, obligatory phytosociological and ecological structure of their species: successional aspect, dispersion syndrome and wood density. Two plots of 1 ha each were built on two nearby islands, on the right bank of the Rio Negro. All trees with PAP (perimeter at breast height) greater than or equal to 30 cm were sampled. The analyzes were carried out by software Fitopac 2.1.2, using the classical phytosociological parameters, the floristic diversity was evaluated by the Shannon - Wiener Diversity Index and the Jaccard Similarity (SJ) was calculated. A total of 1567 records were registered, assigned to 117 species, from 80 genera and 37 families. Most species were represented by only one individual (46%). The Shannon diversity index value was 3.70 and Pielou's Equability (J ') equal to 0.76. Jaccard's similarity index showed high floristic dissimilarity. The largest number of visitors (40%) is concentrated in the diameter class that varies from 10 to 25cm, evidencing the existence of relatively young people in the area. There was a predominance of non-pioneer species (58%), Zoocoria as dispersion syndrome (64%) and high wood density (46%) of the species analyzed. The comparison between the areas demonstrates that there was no change in the predominance of attributes, suggesting that different species may have similar functions in the areas, from the point of view of attributes, since only 21% of the species are matched between the study areas.
Keywords: Áreas de conservação de recursos naturais - Amazônia; Biodiversidade florestal - Amazônia; Comunidades vegetais - Amazônia; CIENCIAS AGRARIAS: RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL; CIENCIAS BIOLOGICAS: BOTANICA; Fitossociologia; Rio Negro; Parque Nacional de Anavilhanas; Ecologia funcional